2017
DOI: 10.1016/j.jceh.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sofosbuvir-Based Direct Acting Antivirals for Hepatitis C in Septuagenarians and Octogenarians

Abstract: Patients aged 70 years or older with genotype 1 achieved high rates of sustained virologic response with treatment with newer sofosbuvir-based DAAs without any undue adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…Moreover, both the SVR rate and rate of discontinuation secondary to AEs were nearly equal in elderly (≥ 75 years) and younger (< 75 years) patients. Although real-world cohort studies demonstrating the effectiveness of several SOF-containing regimens in elderly patients have been published worldwide[ 14 - 16 ], to the best of our knowledge, this is the first real-world study focusing on a high SVR rate and low discontinuation rate due to AEs in Japanese HCV genotype 1 patients aged ≥ 75 years following SOF/LDV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both the SVR rate and rate of discontinuation secondary to AEs were nearly equal in elderly (≥ 75 years) and younger (< 75 years) patients. Although real-world cohort studies demonstrating the effectiveness of several SOF-containing regimens in elderly patients have been published worldwide[ 14 - 16 ], to the best of our knowledge, this is the first real-world study focusing on a high SVR rate and low discontinuation rate due to AEs in Japanese HCV genotype 1 patients aged ≥ 75 years following SOF/LDV therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no consistent upper age cutoff for HCV treatment outlined in the literature, but even among studies of older adults, patients aged 75 years and older remain underrepresented 6,8,16,20 . We describe HCV treatment outcomes with DAAs, with and without ribavirin in patients aged over 75 years treated in three Canadian HCV specialty treatment centers.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of direct‐acting antivirals (DAAs) has opened up treatment to previously difficult‐to‐treat groups, including the elderly 7 . Adults aged 65 years and older were underrepresented in the original phase III licensing studies for most DAA regimens, but data are emerging that DAAs are safe and produce equivalent SVR rates in older adults as younger patients 2,10,11,13,15–17 …”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a study by Snyder et al [13] 2017, concluded that patients aged 70 years or older with genotype 1 achieved high rates of sustained virologic response with treatment with newer sofosbuvirbased DAAs without any undue adverse events.…”
Section: Discussionmentioning
confidence: 99%